Composition of the Volatile Oils of Three Different Species of Artemisia: Composition of volatile oils of Artemisia species - Hassanzadeh Khayyat, Mohammad; Karimi, Hamid (Iranian Journal of Pharmaceutical Sciences, 2005)
The essential oils of the aerial parts of three different Artemisia species (A. scoparia, A. diffusa, A. turanica) growing wildly in the northeast of Iran were analyzed by GC-MS. Twenty-two, twenty-six, and thirteen components were identified in the essential oils of these plants, respectively. The major constituents of the oil of A. scoparia were b-pinene (16.10%), carvacrol (13.81%), limonene (8.82%), cis-ocimene (8.38%), methyl eugenol (7.62%), and transocimene (7.17%). Camphor (25.5%), 1,8-cineol (25.0%), b-thujone (22.%), and a-thujone (6.0%) were the major components identified in the volatile oil of A. diffusa. The main identified compounds in the volatile oil of A. turanica were 1,8-cineol (40.94%), cis-verbenyl acetate (19.03%) and camphor (11.03%). The identified components and their percentages in the essential oil of three different Artimisia species in this study were quite different. Since the chemical composition of the oil depends on various environmental conditions, therefore, these differences can be expected.